"The Reality of Healthcare and Its Role in Social Development" (Comprehensive Journal of Science, 2026)
This study aimed to identify the reality of healthcare and its role in social development through the following axes: recognizing the nature and impact of equitable and comprehensive access to basic healthcare services on key social development indicators, identifying the main challenges facing current healthcare systems and analyzing how these challenges impede comprehensive social development efforts, recognizing the actual role of preventive health programs and health education in fostering social capital and building more cohesive and resilient local communities in the face of health crises, and also identifying effective political mechanisms and strategies that healthcare systems can adopt to integrate the social determinants of health within their priorities, with the aim of reducing health disparities and achieving more sustainable and inclusive social development. The descriptive methodology was followed due to its suitability for the study's purposes.      The study reached the following conclusions:-Comprehensive and equitable access to healthcare is the cornerstone of poverty reduction and the achievement of social justice by providing financial protection for families.-Structural challenges within healthcare systems perpetuate disparities in health outcomes and undermine social development efforts.-Preventive health programs foster social capital and community resilience in facing health crises through building trust and ties.-Sustainable development requires integrated political strategies that address the social determinants of health to radically reduce health inequities.
Keywords: Healthcare, Social Development